Drop jump neuromuscular performance qualities associated with maximal horizontal deceleration ability in team sport athletes - Harper, D. J.; Cohen, D. D.; Rhodes, D.; Carling, C.; Kiely, J. (European Journal of Sport Science, 2022)
The purpose of this study was to investigate associations between, and within, drop jump (DJ) neuromuscular performance (NMP) qualities and maximal horizontal deceleration ability. We also compared DJ NMP qualities in "high" versus "low" horizontal deceleration ability athletes. Twenty-nine university athletes performed: (1) DJs on force plates from 20 (DJ20) and 40 cm (DJ40) heights and (2) maximal horizontal deceleration, measured using radar, following a 20 m acceleration. Maximal horizontal deceleration was evaluated using deceleration (HDEC; m·s-2), across the entire deceleration phase and during early and late deceleration sub-phases. Of the DJ variables assessed, DJ20 and DJ40 reactive strength index (RSI) and concentric mean force had the largest correlations with HDEC (r = -0.54 to -0.61) and the largest differences between high and low HDEC groups (d = 1.20 to 1.40). These correlations were stronger with the early than late HDEC sub-phase (r = -0.54 to -0.66 vs. r = -0.24 to -0.40). Notably, eccentric mean force in DJ40 had large correlations with both DJ20 and DJ40 concentric mean force (r = 0.67 to 0.77), whereas at DJ20 these correlations were small (r = 0.22 to 0.40). Similarly, DJ40 eccentric mean force had a much larger difference between the high and low HDEC groups than DJ20 (d = 1.11 vs. 0.51). These findings suggest DJ RSI from either height may be used as a proxy for HDEC ability, while DJ kinetic analyses should use a higher height to distinguish those with a better capacity to generate eccentric braking forces under increased eccentric loading demands.